2017
DOI: 10.1021/acs.est.7b03039
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Daytime Molecular Chlorine and Nitryl Chloride at a Rural Site on the North China Plain

Abstract: Molecular chlorine (Cl) and nitryl chloride (ClNO) concentrations were measured using chemical ionization mass spectrometry at a rural site over the North China Plain during June 2014. High levels of daytime Cl up to ∼450 pptv were observed. The average diurnal Cl mixing ratios showed a maximum around noon at ∼100 pptv. ClNO exhibited a strong diurnal variation with early morning maxima reaching ppbv levels and afternoon minima sustained above 60 pptv. A moderate correlation (R = 0.31) between Cl and sulfur di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 51 publications
12
116
3
Order By: Relevance
“…The proposed source originated from photolysis of 20 ClNO 2 generating chlorine radicals, which can oxidize VOC to RO 2 . However, the observed ClNO 2 (0.5 ppbv, maximum of diurnal average, Tham et al, 2016) and Cl 2 (Liu et al, 2017) concentrations could only explain 10% and 30% of the missing primary RO x source for the summer Wangdu campaign (Tan et al, 2017). During the winter campaign in Beijing, the missing primary RO x source was 2 to 3 times larger than what was found during the Wangdu summer campaign.…”
Section: Model-measurement Comparison Of Peroxy Radicals Concentratiomentioning
confidence: 89%
“…The proposed source originated from photolysis of 20 ClNO 2 generating chlorine radicals, which can oxidize VOC to RO 2 . However, the observed ClNO 2 (0.5 ppbv, maximum of diurnal average, Tham et al, 2016) and Cl 2 (Liu et al, 2017) concentrations could only explain 10% and 30% of the missing primary RO x source for the summer Wangdu campaign (Tan et al, 2017). During the winter campaign in Beijing, the missing primary RO x source was 2 to 3 times larger than what was found during the Wangdu summer campaign.…”
Section: Model-measurement Comparison Of Peroxy Radicals Concentratiomentioning
confidence: 89%
“…In contrast, for the NCP samples, we found a median NR of 0.7, which indicated that particles were quite acidic for a major part of the measurement period. Similarly, Liu et al (2017) determined the particle pH values for NCP to be typically in the range of 2.8 to 4.8, but even reached down to pH values of 2 during daytime. Such extremely acidic conditions might be necessary for the formation of SQT-OSs, and thus, explain the contrasting trends observed for MEL and NCP.…”
Section: Correlations Of Mt-oss and Sqt-ossmentioning
confidence: 96%
“…Ambient ClNO 2 was first observed off the coast of Texas in 2006 . It has since been measured from ship-, ground-, and aircraft-based platforms in both continental and coastal/marine environments throughout North America (Edwards et al, 2013;Faxon et al, 2015;Kercher et al, 2009;Kim et al, 2014;Mielke et al, 2011Mielke et al, , 2016Osthoff et al, 2008;Riedel et al, 2012Riedel et al, , 2013Thornton et al, 2010;Wild et al, 2016;Young et al, 2012), Europe and the United Kingdom (Bannan et al, 2015(Bannan et al, , 2017Phillips et al, 2012Phillips et al, , 2016Reyes-Villegas et al, 2018), and Asia (Liu et al, 2017;Tham et al, 2018Tham et al, , 2016Tham et al, , 2014X. Wang, Wang, Xue, et al, 2017;T.…”
Section: Introductionmentioning
confidence: 99%